Program Kiah: Meningkatkan Motorik Halus Pada Anak Down Syndrome (SLB C DHARMA RENA RING PUTRA 1 YOGYAKARTA) - Atika Nurhaliza; Syafna Naziiza (CV. ITTC INDONESIA, 2024)
Down Syndrome children experience delays in fine motor development. This is caused by physical and mental abnormalities due to disruption of genetic information. This study aims to improve fine motor skills in Down Syndrome children through the KIAH program (Karya Indah Anak Hebat) with the method of painting using watercolor. This research uses a qualitative method with a phenomenological approach conducted by involving 5 Down Syndrome children at SLB C Dharma Rena Ring Putra 1 Yogyakarta through observation, interviews, and documentation. The KIAH Program with the method of painting with Down Syndrome children can improve the fine motor skills of Down Syndrome children by paying attention to the process and results of their paintings.